Bentuk Ketidakutuhan Gagasan Kalimat dalam Buku Ajar Bahasa Indonesia Kelas 7 Tahun 2023 TIM MGMP Kabupaten Magetan - Della Velia; Suhartono Suhartono; Andik Yuliyanto (Journal on Education, 2024)
This research aims to describe the ineffectiveness of sentences in the form of incomplete ideas in the 2023 class 7 Indonesian language textbook by the Magetan Regency MGMP team. The method used is descriptive qualitative with data in the form of incomplete sentences. The data comes from the 2023 class 7 Indonesian language textbook by the Magetan Regency MGMP team which was collected using note-reading and library research techniques. The data analysis used is a descriptive analysis technique by describing sentences that are indicated as not having a complete idea. The research results showed that the incompleteness of the sentence ideas in the textbook was found in 21 sentences which were categorized into six forms: (1) incomplete (hanging) sentences; (2) there is no object accompanying the transitive active verb; (3) sentences without subject; (4) sentences without predicates; (5) sentences without subject and predicate; and (6) the sentence does not have a main clause (main sentence). Thus, it is hoped that this research can contribute to improving the quality of Indonesian language textbooks and support a more effective learning process.